What is Normal? Neuromuscular junction reinnervation after nerve injury. Issue 5 (23rd August 2019) - Vannucci, Bianca; Santosa, Katherine B.; Keane, Alexandra M.; Jablonka‐Shariff, Albina; Lu, Chuieng‐Yi; Yan, Ying; MacEwan, Matthew; Snyder‐Warwick, Alison K.
Abstract: Introduction: In this study we present a reproducible technique to assess motor recovery after nerve injury via neuromuscular junction (NMJ) immunostaining and electrodiagnostic testing. Methods: Wild‐type mice underwent sciatic nerve transection with repair. Hindlimb muscles were collected for microscopy up to 30 weeks after injury. Immunostaining was used to assess axons (NF200), Schwann cells (S100), and motor endplates (α‐bungarotoxin). Compound motor action potential (CMAP) amplitude was used to assess tibialis anterior (TA) function. Results: One week after injury, nearly all (98.0%) endplates were denervated. At 8 weeks, endplates were either partially (28.3%) or fully (71.7%) reinnervated. At 16 weeks, NMJ reinnervation reached 87.3%. CMAP amplitude was 83% of naive mice at 16 weeks and correlated with percentage of fully reinnervated NMJs. Morphological differences were noted between injured and noninjured NMJs. Discussion: We present a reproducible method for evaluating NMJ reinnervation. Electrodiagnostic data summarize NMJ recovery. Characterization of wild‐type reinnervation provides important data for consideration in experimental design and interpretation.